Genetic Data for Merlin (Falco columbarius) and Cross-Species Microsatellite Amplification in Select Falco Species, North America ... - Kevin Sage; Barbara J Pierson; Sarah A Sonsthagen; Megan C Gravley; Sandra L Talbot (U.S. Geological Survey, 2020)
This data set contains allele sizes for 8 previously published and 16 novel microsatellite loci, and one microsatellite redesigned for amplification in Merlins (Falco columarius) associated with circadian clock control and polymorphism that has been associated with juvenile dispersal and migratory behavior in some avian species for Merlin (Falco columbarius) from North America (n=21). Allele sizes for the 16 microsatellite loci developed in this study are included for 12 Gyrfalcons (F. rusticolus) and 13 Peregrine Falcons (F. peregrinus). Additional population level data for Merlins and mtDNA will be added to this data release in the future. ...